A study on free-floating carsharing in Europe: Impacts of car2go and DriveNow on modal shift, vehicle ownership, vehicle kilometers traveled, and CO₂ emissions in 11 European cities - Hansjörg Fromm; Lukas Ewald; Dominik Frankenhauser; Axel Ensslen; Patrick Jochem (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2019)
Free-floating carsharing, i.e., carsharing that allows pick-up and return of a car anywhere within a specified area in a city, has now been available in European cities for more than 10 years. As an important example of the sharing economy, carsharing strives for a more efficient use of resources with positive economic, social, and environmental impacts. After a decade of operation and user experience, an evaluation seems appropriate. car2go and DriveNow, who merged into SHARE NOW in 2019, are the largest carsharing operators in the world. They commissioned this study to identify the impact of carsharing on vehicle holdings, modal shift, vehicle kilometers traveled (VKT), and greenhouse gas emissions. The study was conducted in 2018 and 2019. It is based on a survey among car2go and DriveNow customers in 11 European cities. A previous study was performed by the University of California, Berkeley, for 5 North American cities in 2016 [7]. [...]
Keywords: 330